Application possibilities of selection indices in Pannon White rabbits' breeding programme. Issue 4 (2nd October 2018) - Ács, Virág; Szendrő, Katalin; Garreau, Hervé; Donkó, Tamás; Matics, Zsolt; Nagy, István
Abstract: Genetic parameters for 21-d litter weight (LW21) and thigh muscle volume (TMV) were estimated, and based on these traits a two-trait selection index was created with the purpose of increasing the efficiency of the Pannon White rabbits' breeding programme. Litter weight at 21 d of age (LW21, n  = 22, 002) and thigh muscle volume (TMV, n  = 8124) measurements (based on computed tomography – CT) were analysed that were recorded between 1992 and 2016. The evaluated animals were reared in 4178 litters and the total number of rabbits involved in the pedigree file was 14, 124. LW21 and TMV records were analysed jointly in a two-trait animal model. The estimated heritability for LW21 and TMV were 0.10 ± 0.01 and 0.21 ± 0.02, respectively, and the estimated genetic correlation between these traits was −0.24 ± 0.07. The common environmental effect had the same magnitude (0.10 ± 0.01) as the additive genetic effect. The created selection index constructed to have 50 and 50% contribution of the measured traits. Application possibility of the created index was tested on a given kindling batch. In this case, the first step of the selection procedure was performed either according to the current breeding programme (based on the LW21 breeding values) or based on the two trait selection index. The second step of selection was not changed (based on the TMV breeding values). The consequences of using index scores instead of the regular procedure were obtaining 27.8% higher average breeding value for TMV and 11.4% lower average breeding value for LW21. These results suggest that introduction of the index may improve economic efficiency.